Penerapan Manajemen Konflik Terhadap Kedisiplinan Pegawai - Volasofia Yustikasari; Mila Lutfiana Asshofa; Abdul Jalil Jawhari (Intizam, Jurnal Manajemen Pendidikan Islam, 2022)
Humans as social beings have a strong urge to always live together. In everyday life, humans cannot be separated from the terms behavior and attitudes. Discipline is the most important function of Human Resource Management (HRM) and serves as a benchmark to determine whether other Human Resource Management (HRM) functions have been implemented properly or not. Good employee discipline reflects that other Human Resource Management (MSDM) functions have been carried out according to plan. Conversely, if employee discipline is not good, it means that the implementation of Human Resource Management (HRM) functions in the organization is also not good. If there is a conflict related to employee discipline, then a leader must act immediately to resolve the conflict. Negative conflicts must be solved or resolved as soon as possible, while positive conflicts are maintained to spur increased productivity or organizational performance. Conflict can be minimized and becomes a positive thing if there is a leader in the organization who is able to manage conflict well. Thus conflict can be negative or positive depending on how the leader handles it. Since the ultimate goal of an organization is the welfare of the elements in it, while this welfare can be achieved if the productivity or performance of the organization can be continuously improved.